SNOUCK HURGRONJE: CLOSED FRIEND OR OPPONENT FOR MUSLIM IN INDONESIA? - Setiawan, Iwan setiawan (Jurnal Tamaddun: Jurnal Sejarah dan Kebudayaan Islam, 2025)
It is undeniable, the figure of Snouck Hurgronje is still an interesting character to study. Is he friend or opponent to Muslims? For Islamic scholars, he is the ideal figure of a researcher and practitioner who has successfully used the results of his research on Acehnese society during the Aceh war. The results of his research were then used by Snouck Hurgronje in breaking the resistance of the Acehnese people. On the other hand, for the Indonesian Muslim community, he is a representation of the orientalist figure who is most hated by Muslims. Especially in Indonesia. The representation of Snouck Hurgronje is a scientist who is devoted to destroying Islam. o this day, the stigma of â€œSnouckismâ€ or people trying to destroy Islam still exists. This paper attempts to describe the intellectual biography of Snouck Hurgronje to his advice related to the issues of Islamic politics in Aceh, the politics of Hajj, the Islamic Community and Islamic Law. By examining Snouck Hurgronje's thoughts on this matter, it will be known how Snouck Hurgronje's view of Islam really is.